The Effect of The Proposed Recreational Sports Program in Reducing The Degree Depression Among Students with hearing Impaired Adolescents - yassine heddal (sports creativity, 2025)
The aim of this study was to identify the effect of the proposed recreational sports program in reducing the degree of depression among adolescents with hearing impairments. The researchers relied on the experimental method using the “Birleson” Depression Scale and a proposed sports program on a sample of 12 students with a hearing disability of both sexes. The researchers found the following results: - The recreational sports program has the effect of reducing the degree of depression among students with hearing impaired adolescents.